Models of classroom assessment for course-based research experiences - Hanauer, David I.; Zhang, Tong; Graham, Mark J.; Adams, Sandra D.; Ahumada-Santos, Yesmi Patricia; Alvey, Richard M.; Antunes, Mauricio S.; Ayuk, Mary A.; Elena Báez-Flores, María; Bancroft, Christa T.; Bates, Tonya C.; Bechman, Meghan J.; et al. (Frontiers in Education, 2023)
Course-based research pedagogy involves positioning students as contributors to authentic research projects as part of an engaging educational experience that promotes their learning and persistence in science. To develop a model for assessing and grading students engaged in this type of learning experience, the assessment aims and practices of a community of experienced course-based research instructors were collected and analyzed. This approach defines four aims of course-based research assessment – 1) Assessing Laboratory Work and Scientific Thinking; 2) Evaluating Mastery of Concepts, Quantitative Thinking and Skills; 3) Appraising Forms of Scientific Communication; and 4) Metacognition of Learning – along with a set of practices for each aim. These aims and practices of assessment were then integrated with previously developed models of course-based research instruction to reveal an assessment program in which instructors provide extensive feedback to support productive student engagement in research while grading those aspects of research that are necessary for the student to succeed. Assessment conducted in this way delicately balances the need to facilitate students’ ongoing research with the requirement of a final grade without undercutting the important aims of a CRE education.